Effect of Gross Domestic Regional Bruto, Provincial Minimum Wage, and Investment on Labor Absorption - Jaya, Tiara Juliana; Kholilah, Kholilah (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
The unemployment rate in Indonesia is a classic problem that continues to be reviewed. This study aims to determine the impact of gross domestic product, provincial minimum wage, and labor absorption investment. This research uses quantitative methods and panel data analysis, which is processed using eviews 10, conducted in six provinces in Java in 2013-2019. The study used secondary data from the central statistics agency: labor absorption data, gross regional domestic product, and the provincial minimum wage (UMP). At the same time, investment data obtained the value of domestic investment and foreign investment. The results showed that PDRB and investment had a positive effect on labor absorption. In contrast to these two variables, UMP negatively affects labor absorption. The results of this study are essential for policymakers on labor issues in Indonesia. The suggestion for the next research is to use a broader scope, namely Indonesia. Besides, it is necessary to distinguish the workforce into an educated workforce, a trained workforce, an uneducated workforce, and an untrained workforce.